MEMBANGUN KOMUNITAS MEREK PADA TOYOTA-COROLLA CLUB - Nidjat Ibrahim; Nia Rosalinda (Media Riset Bisnis & Manajemen, 2005)
A community is formed from feeling to be unity between partof agroup and goad relationship between them. Community tends to be identified as base on behavior or identification between parts of a group. The purpose of this research is to analyze how to build brand community at Toyota Corolla Club. SEM (Structural Equation Model) is used in this research using AMGS 4.0. Result of this research is the integration in community is a function of good relationship experienced by customers, brand, firm and another customer. Because of that, we suggest to supplier or sales manager to take part in build brand community in order to increase total revenue.